Psychology and constructivism in international relations : an ideational alliance - Shannon, Vaughn P.; Kowert, Paul, 1964- (Ann Arbor : University of Michigan Press, 2012)
Constructivist IR scholars study the ways in which international norms, culture, and identities-all intersubjective phenomena-inform foreign policy and affect the reaction to and outcomes of international events. Political psychologists similarly investigate divergent national self-conceptions as well as the individual cognitive and emotional propensities that shape ideology and policy. Given their mutual interest in human subjectivity and identity politics, a dialogue and synthesis between constructivism and political psychology is long overdue. The contributors to this volume discuss both theoretical and empirical issues of complementarity and critique, with an emphasis on the potential for integrating the viewpoints within a progressive ideational paradigm. Moreover, they make a self-conscious effort to interrogate, rather than gloss over, their differences in the hope that such disagreements will prove particularly rich sources of analytical and empirical insight.
Introduction: ideational allies psychology, constructivism, and international relations / Vaughn P. Shannon -- Completing the ideational triangle: identity, choice, and obligation in international relations / Paul A. Kowert -- How identities form and change: supplementing constructivism with social psychology / Deborah Welch Larson -- Norms and the management of identities: the case for engagement between constructivism and the social identity approach / Jodie Anstee -- Identity and decision making: toward a collaborative approach to state action / Asli Ilgit and Binnur Ozkececi-Taner -- Re-constructing development assistance: analogies, ideas, and norms at the dawn of the new millennium / Marijke Breuning -- Agent-level and social constructivism: the case of the iran hostage crisis / David Patrick Houghton -- Determinants of security and insecurity in international relations: a cross-national experimental analysis of symbolic and material gains and losses / Peter Hays Gries, Kaiping Peng, and H. Michael Crowson -- Psychology and constructivism: uneasy bedfellows? / Rose McDermott and Anthony Lopez -- Conclusion: context and contributions of the ideational alliance / Paul A. Kowert.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
English.
JSTOR
Keywords: International relations -- Psychological aspects; Group identity -- Political aspects; Constructivism (Philosophy); Relations internationales -- Aspect psychologique; Identité collective -- Aspect politique; Constructivisme (Philosophie); POLITICAL SCIENCE -- Globalization; POLITICAL SCIENCE -- International Relations -- Diplomacy; Constructivism (Philosophy); Group identity -- Political aspects; International relations -- Psychological aspects